Desarrollo de un aplicativo web para el análisis de competencias Semat de un equipo de desarrollo de proyectos de Sistemas de Información Geográfica (2019)
There are certain conditions in the work teams, which is important to keep in mind to allow effective performance. One of these conditions is the set of skills, knowledge and personality characteristics of each individual. During the development cycle of the Geographic Information System (GIS) projects, the intervention of different people is evidenced, which individually or in groups have certain roles and specific tasks within the work team in the development of the phases. Therefore, it is important to consider the different characteristics of each individual (personality, skills, knowledge), because these characteristics guide teamwork and how they complement each other. In addition, better technical cooperation and work agility is presented. Semat (Theory and Method of Software Engineering) includes a core of accepted and proven elements of good software development practices, including the competencies of members of the GIS project development team. Regarding the use of Semat in the formation of work teams for the development of GIS projects, use should be made of a dictionary characterized within Semat, which allows recognizing the skills sought in each individual for a specific position within of the team, this in order to get more benefit in terms of the personal skills of each member, which will increase the ease with which teams are formed to develop GIS projects that meet the characteristics you need and allow more results efficient and higher productivity